Faktor-Faktor Yang Mempengaruhi Produktivitas Kerja Karyawan PT. Jumbo Power International - M. Renandi Ekatama; Desmon Desmon; Armalia Reny WA; Andi Surya (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The data for this study were collected by distributing questionnaires to 52 respondents. The sampling method used is purposive sampling. The data obtained is primary data which is the result of respondents' answers to questionnaires distributed to respondents. The statistical method used is multiple regression. The results showed that (1) Discipline has a positive and significant effect on productivity. This is indicated by the partial regression results, namely a significance value of 0.001 <0.05 and a t value of 3.499 which is greater than the t table of 2.011. (2) Motivation has a positive and significant influence on productivity. This is indicated by the partial regression results, namely a significance value of 0.001 <0.05 and a t value of 3.478, greater than the t table of 2.011. (3) Compensation has a positive and significant effect on productivity. This is indicated by the partial regression results, namely a significance value of 0.020 <0.05 and a t-value of 1.729 which is smaller than the t-table of 2.011. The results found that discipline and motivation have a positive and significant effect on productivity, and compensation has no positive and insignificant effect on productivity.